菜籽油脱胶和脱臭工艺优化Optimization of rapeseed oil degumming and deodorization process - 洪坤强1，2，罗质1，叶展3，雷芬芬1，2，钟武1，2，何东平1，2 HONG Kunqiang1,2, LUO Zhi1, YE Zhan3, LEI Fenfen1,2, ZHONG Wu1,2, HE Dongping1,2 (Zhongguo youzhi, 2024)
为了对菜籽油适度精炼提供参考，以菜籽原油（磷含量693.00 mg/kg)为原料，采用磷脂酶A1(PLA1)进行预脱胶，再采用磷脂酶C(PLC)进行复脱胶，所得脱胶油采用低温短时两级捕集回流脱臭工艺进行脱臭。以磷含量为指标，通过单因素试验和响应面试验对PLA1预脱胶工艺条件进行优化。以生育酚损失率为指标，通过单因素试验和正交试验对脱臭工艺条件进行优化。另外，对比了不同脱胶方法（PLA1-PLC复合脱胶、PLC脱胶、水化脱胶）和不同脱臭工艺（低温短时两级捕集回流脱臭工艺和常规脱臭工艺）的效果。结果表明：PLA1预脱胶最优工艺条件为柠檬酸（45 g/100 mL）添加量3.3 mL/kg、PLA1(10 U/mL) 添加量44.0 mL/kg、脱胶温度54.0 ℃、脱胶时间1.4 h，在此条件下PLA1-PLC复合脱胶菜籽油中磷含量相比菜籽原油下降了（99.01±0.05）%；与其他脱胶方法相比，PLA1-PLC复合脱胶法脱胶效率高；脱臭最优工艺条件为脱臭温度220 ℃、脱臭时间80 min，在此条件下生育酚损失率在10%以下，且各生育酚单体的相对含量基本不变；与常规脱臭工艺相比，低温短时两级捕集回流脱臭工艺具有能耗和生育酚损失率低的优点。综上，PLA1-PLC复合脱胶和低温短时两级捕集回流脱臭工艺可以较好地改善菜籽油的品质，具有良好的市场应用前景。To provide a reference for the moderate refining of rapeseed oil, crude rapeseed oil (693.00 mg/kg of phosphorus) was used as raw material, PLA1 was used for pre-degumming, and then PLC was used for re-degumming, and the degummed oil was deodorized by low-temperature short-term two-stage capture reflux deodorization process. The PLA1 pre-degumming process was optimized by single factor experiment and response surface methodology with phosphorus content as index. The deodorization process was optimized by single factor experiment and orthogonal experiment with tocopherol loss rate as index. In addition, the effects of different degumming methods ( PLA1-PLC composite degumming, PLC degumming, hydration degumming ) and different deodorization processes ( low-temperature short-term two-stage capture reflux deodorization process and conventional deodorization process) were compared. The results showed that the optimal process conditions for PLA1 pre-degumming were as follows: citric acid (45 g/100 mL) dosage 3.3 mL/kg, PLA1 (10 U/mL) dosage 44.0 mL/kg, degumming temperature 54.0 ℃, and degumming time 1.4 h. Under the optimal conditions, the phosphorus content of PLA1-PLC composite degummed rapeseed oil decreased (99.01±0.05)% compared with crude rapeseed oil. Compared with other degumming methods, PLA1-PLC composite degumming method had higher degumming efficiency. The optimal deodorization conditions were deodorization temperature 220 ℃ and deodorization time 80 min. Under the optimal conditions, the tocopherol loss rate was less than 10%, and the relative content of each tocopherol monomer remained basically unchanged. Compared with the conventional deodorization process, the low-temperature short-term two-stage capture reflux deodorization process had the advantages of low energy consumption and low tocopherol loss rate. In summary, the PLA1-PLC composite degumming and low-temperature short-term two-stage capture reflux deodorization processes can improve the quality of rapeseed oil and have a good market application prospect.